Angular analysis of B0 → K*0e+e − decays - The LHCb collaboration; R. Aaij; A. S. W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A. A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C. A. Aidala; et al. (Journal of High Energy Physics)
Abstract An angular analysis of B 0 → K *0 e + e − decays is presented using proton-proton collision data collected by the LHCb experiment at centre-of-mass energies of 7, 8 and 13 TeV, corresponding to an integrated luminosity of 9 fb −1. The analysis is performed in the region of the dilepton invariant mass squared of 1.1–6.0 GeV2/c 4. In addition, a test of lepton flavour universality is performed by comparing the obtained angular observables with those measured in B 0 → K *0 μ + μ − decays. In general, the angular observables are found to be consistent with the Standard Model expectations as well as with global analyses of other b → sℓ + ℓ − processes, where ℓ is either a muon or an electron. No sign of lepton-flavour-violating effects is observed.